1984
DOI: 10.1007/bf01852386
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic studies on cimetidine and ranitidine in anesthetized dogs

Abstract: The cardiovascular effects of the H2-receptor-antagonists cimetidine and ranitidine have been compared in a randomized double-blind crossover study. The experiments were performed in seven anesthetized mongrel dogs. Cimetidine (200 mg) and ranitidine (50 mg) were infused i.v. for 2 min. The time interval between cimetidine and ranitidine application was always 3 h. The direct comparison of the drug effects on blood pressure shows a significant difference between cimetidine and ranitidine (P less than 0.001). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…We observed, however, that ranitidine at a dose of 3.0 mg/kg sometimes caused dogs to collapse, and in the anesthetized dogs ranitidine at a dose of 3.0 mg/kg markedly decreased the blood pressure. Previous reports have also shown that cimetidine and ranitidine induce hypotension (25)(26)(27), although such a severe decrease in blood pressure was not observed. Since the decrease in blood pressure was not shown in the case of famotidine, anticholinesterase activity may also he involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 75%
“…We observed, however, that ranitidine at a dose of 3.0 mg/kg sometimes caused dogs to collapse, and in the anesthetized dogs ranitidine at a dose of 3.0 mg/kg markedly decreased the blood pressure. Previous reports have also shown that cimetidine and ranitidine induce hypotension (25)(26)(27), although such a severe decrease in blood pressure was not observed. Since the decrease in blood pressure was not shown in the case of famotidine, anticholinesterase activity may also he involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 75%
“…the circular system, gland secretion, intestinal transit, and defecation as adverse events. It has been reported that neostigmine, cimetidine, and ranitidine decrease blood pressure in experimental animals [21,23]. Both in non-clinical and clinical studies on nizatidine, no severe AChE inhibition-related adverse events including a fall in blood pressure and severe diarrhea have been observed [24,25].…”
Section: Discussionmentioning
confidence: 99%